Digoxin mitigates diethylnitrosamine-induced acute liver injury in mice via limiting production of inflammatory mediators - Mohamed E. Shaker; Mohamed F. Hamed; Ahmed A. Shaaban (Elsevier, 2022)
The cardiotonic digoxin has been recently shown to possess an anti-inflammatory potential in numerous metabolic and inflammatory disorders. However, data about digoxin's impact in the setting of acute liver injury and sterile inflammation are still limited. Here, we investigated the potential effect of digoxin pretreatments (0.25 and 0.5 mg/kg, oral) on the severity of acute hepatotoxicity in mice challenged with a single dose of diethylnitrosamine (DN; 150 mg/kg, intraperitoneal) for 24 h. Our results indicated that digoxin pretreatments dose-dependently mitigated DN-induced rise of hepatocellular injury parameters and necroinflammation scores. Digoxin, particularly at dose of 0.5 mg/kg, boosted the number of PCNA positive hepatocytes, leading to improvement of the reparative potential in hepatocytes of DN-intoxicated livers. Digoxin's ameliorative effect on DN-hepatotoxicity coincided with (i) lowering the increased hepatic production and release of the proinflammatory mediators IL-17A, IL-1β and TNF-α, and (ii) impeding the attraction and infiltration of monocytes to the liver, as denoted by decreasing serum MCP-1 and F4/80 immunohistochemical expression. These effects were attributed to reducing DN-induced activation of NF-κB and overexpression of CD98 in the liver. Meanwhile, DN elicited a decline in the hepatic production and release of the anti-inflammatory cytokines IL-22 and IL-6, which was intensified by digoxin, especially at a dose 0.5 mg/kg. In conclusion, digoxin conferred liver protection against DN-insult by impairing the overproduction of proinflammatory cytokines and infiltration of inflammatory cells to the liver.